Development of E-LKPD Using the Wizer.me Website Based on Discovery Learning in Science and Technology Learning in Class IV Elementary Schools - Lara Syafira; Yeni Erita (STKIP Taman Siswa Bima, 2025)
The development of E-LKPD based on the Wizer.me platform with the Discovery Learning model is the aim of this research. It is designed for use in science learning in fourth grade elementary schools. This research is motivated by the fact that LKPD are still in printed form, these LKPD are usually plain, less interesting, and do not encourage students to participate actively in the learning process. In addition, the use of technology in providing learning materials that suit modern educational needs is still limited. For this research, the ADDIE model is used as a Research and Development (R&D) approach, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. Validation by material, language and media experts gave a score of 93.54% so that the product was included in the